Treatment of HeartMate III–LVAD driveline infection by negative pressure wound therapy: Result of our case series. Issue 11 (November 2021) - Cikirikcioglu, Mustafa; Ponchant, Kevin; Murith, Nicolas; Meyer, Philippe; Yilmaz, Nurcan; Huber, Christoph
Driveline infection is one of the most frequent complications following left ventricular assist device (LVAD) treatment and there is no consensus for its management. The standard approach to treat foreign-body infection is complete device ablation, which is not always feasible and therefore not an elected method for LVAD driveline infections. Here we share the results from a series of cases successfully treated for driveline infection by negative pressure wound therapy (NPWT) therapy. Between 2016 and 2020, five male patients were hospitalized in our unit with a driveline infection of HeartMate III-LVAD ® . Ultrasonography and/or thoraco-abdominal CT confirmed the diagnosis, infection localization, and abscess formation. Following an antibiotic treatment, an urgent surgical abscess drainage and debridement of the infected tissues were performed. At the end of the procedure, NPWT was applied. NPWT re-dressing and debridement of wound was performed every 3–4 days. The wound was closed surgically after obtaining negative culture results and good healing. The patients were discharged in good condition, without signs of infection. Two patients underwent successful heart transplantation after 1 and 13 months. Other patients did not show any residual or recurrent infection during the follow-up within 25 months. Driveline infection following LVAD implantation is a significant complication and a challenging in terms of management for both; the surgical team and the patient. These results from our case series report a successful and less invasive approach by using NPWT for the treatment of LVAD driveline infections.